Structure Optimization Analysis for Complex Rail Vehicle Body Based on Sub-model - YU Mingyang; MI Caiying (机车电传动)
The longitudinal rod, a key structure in the middle of a complex rail vehicle body’s underframe, was respectively dispersed into the solid element and shell element in the structure strength analysis for the whole body based on the operation condition of longitudinal compression, as well as the difference and defects of the two conventional modeling methods were indicated. In order to solve the problems of conventional modeling methods, it’s presented that using solid element to disperse longitudinal rod and its surrounding parts in the sub-model to receive precise result, which was helpful for the structure optimization analysis. The results showed: using sub-model technology, in the proceed of analyzing structure strength of the complex rail vehicle body, could obtain more accurate result efficiently with proper cut-boundary; In the design of body structure, taking more consideration on the coordination of the structure stiffness was beneficial to improve the body structure strength.